The Role of Beetroot Juice in Increasing Hemoglobin Levels of Pregnant Women: An Educational Approach to Nutritional Interventions in Health Science Education - Wintarsih Wintarsih; Emiliyasari Emiliyasari; Lena Feni Hariyani; Mefti Hariyani; Nofrisa Nofrisa; Yulia Nurhayani (Postgraduate, University of Mataram, 2025)
Anemia during pregnancy is a significant health problem that affects both the mother and fetus. Iron deficiency, as the primary cause, can lead to complications such as premature birth and maternal and neonatal mortality, especially in areas with limited access to adequate nutrition, like Enim Estuary Regency. A natural solution, such as the consumption of beetroot juice, which is rich in iron, folic acid, and vitamin C, has emerged as an alternative for increasing maternal hemoglobin levels during pregnancy. This study aims to assess the effectiveness of beetroot juice consumption in increasing maternal hemoglobin levels at the Tanjung Raya Community Health Center. The research also aims to identify the characteristics of pregnant women, analyze their hemoglobin levels before and after the intervention, and evaluate the difference in mean hemoglobin levels following beetroot juice consumption. This study employs a quantitative approach with a quasi-experimental design using a one-group pretest-posttest format. The study involved 150 pregnant women, selected through total sampling at the Tanjung Raya Community Health Center. The independent variable is beetroot juice consumption, while the dependent variable is hemoglobin (Hb) levels. Data were analyzed using the Wilcoxon Signed Rank Test. The results show that the majority of respondents (93.33%) were aged between 20 and 40 years, with an even distribution across the three trimesters of pregnancy. Regarding education, the majority had completed junior high school and high school (28% each). The analysis revealed a significant improvement in maternal Hb levels after the intervention, indicating that beetroot juice consumption is effective in increasing hemoglobin levels in anemic pregnant women. It is recommended that the Tanjung Raya Community Health Center integrate beetroot juice consumption into their maternal health improvement programs and enhance educational efforts regarding the benefits of consuming nutritious foods